Competition Analysis of Primagama Yogyakarta Tutoring Institute - Hartini Prasetyo Wulandari (Syntax Corporation Indonesia, 2023)
One thing that makes this research necessary is that in the midst of this increasingly fierce competition, in addition to always realizing the motto of its vision, and mission, Primagama Education Institution has also set a target that by 2006 Primagama must have been present in all capitals / districts / cities / sub-districts throughout Indonesia. In addition, Primagama must also always maintain an average turnover growth every year of around 35% compared to the previous year. This research was conducted at the Primagama Educational Institute Jogjakarta to determine the preparation of competitive advantage strategies used in facing competition and achieving targets that have been set in each period. The data collection method is carried out face-to-face with managers and field heads to obtain field data or primary data by providing a list of questions (questionnaires). Conclusions that can be drawn from the market growth strategy / tutoring products applied to increase market share by the Primagama Jogjakarta Education institution include: Judging from the results of the SWOT analysis, internal factors that are strengths for the Primagama Jogjakarta Education Institute.